Construction of indolenine-substituted spiro[pyrrolidine-2, 3′-oxindoles] from 2-alkenylindolenines and isatin-derived azomethine ylides. Issue 19 (10th May 2018) - Cui, Longchen; Zhu, Guodong; Liu, Siyuan; Bao, Xiaoze; Zhao, Xiangyu; Qu, Jingping; Wang, Baomin
Abstract: An organic base-catalyzed 1, 3-dipolar cycloaddition between 2-alkenylindolenines and azomethine ylides derived from isatins and benzylamines was successfully developed to assemble indolenine-substituted spiro [pyrrolidine-2, 3′-oxindole] ring systems. Generally, good regioselectivities (up to 14:1 rr ) and high yields (up to 91%) were obtained under mild conditions. Graphical abstract: